1963
DOI: 10.1149/1.2425813
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of Dispersion-Hardened Nickel-Al[sub 2]O[sub 3] Alloys

Abstract: normalNickel‐Al2O3 alloys were electrodeposited from a Watt's‐type nickel‐electrolyte, which contained the second phase particles suspended in the solution. The effects of particle concentration, particle size, and plating conditions on microstructure and physical properties of the deposits were studied. Using submicroscopic Al2O3 particles, the room temperature yield strength increased from 8 kg/mm2 for pure nickel to 35 kg/mm2 for alloys containing 3.5–6.0 v/o (volume per cent) normalAl2O3 . It is believ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

1984
1984
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(40 citation statements)
references
References 1 publication
1
38
0
1
Order By: Relevance
“…Sautter [19] found that the volume percentage of A1203 particles in a nickel matrix increases, with increasing particle concentration in the bath. This behaviour was confirmed by further investigators for a wide range of metal particle systems [8,10,12,14,16,[20][21][22][23][24][25][26][27][28][29][30].…”
Section: Particle Concentration Type Shape and Sizementioning
confidence: 99%
“…Sautter [19] found that the volume percentage of A1203 particles in a nickel matrix increases, with increasing particle concentration in the bath. This behaviour was confirmed by further investigators for a wide range of metal particle systems [8,10,12,14,16,[20][21][22][23][24][25][26][27][28][29][30].…”
Section: Particle Concentration Type Shape and Sizementioning
confidence: 99%
“…A commercially available electrolytic cell ͑Yamamoto-MS Co. Ltd., model I with internal dimensions of 65 ϫ 65 ϫ 95 mm͒ was used. The volume of the plating bath was 250 cm 3 . Both pure copper ͑JIS C1201P͒ and stainless steel ͑JIS SUS304͒ plates with exposed surface areas of 10 cm 2 (3 ϫ 3.33 cm͒ were used as substrates.…”
Section: Methodsmentioning
confidence: 99%
“…It has been found that alumina will codeposit with copper readily from a F '4 cyanide bath (23) but not from an acid ..w s sulphate bath (23,24,25). Hoorever, the same powder is reported to codeposit easily with nickel (23,26,27) and iron (28) Guglielmi (29) has claimetl that in nickel sulphamate electrolytes, codeposition of Bilicon carbide is increased by increase in current density but that of titania is decreased.…”
Section: Factors Affecting Particle Codepositionmentioning
confidence: 98%